AN ACCOUNTING COURSE FOR MAJORS AND NON-MAJORS. - Yankee, Glen G.; Rosenfeld, Eugene; Ledley, Ralph G. (The Accounting Review, 1961)
This article focuses on an accounting course for majors and non-majors. The standard elementary accounting text is designed to suit the needs of accounting majors only. Such a text necessarily contains much technical material and is designed for two 3-credit courses covering one academic year. Hence at institutions where only a standard course is offered, many students with a less than professional interest in accounting are probably discouraged from taking any accounting courses. The standard text starts with the assumption that the student has no knowledge of accounting and very little knowledge of business practice. It takes him through as much theoretical and practical material as can be fitted into that period of time, theory and practice being blended or alternated. Neither can be properly studied without the other. A student who really wants merely an introduction to accounting and business practice must, therefore, ordinarily take a full year course. This problem points up the need for a one year course, the first semester of which will serve as a survey course for the non-accountants as well as an introductory course for the accounting major.